Self-Esteem and Social Support on Resilience Female Prisoners - Cholili, Abd Hamid; Karimah, Putri Miatul (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
At the beginning of the prison, prisoners feel sad, have no enthusiasm to live their lives, and cannot make peace with the situation. The phenomenon that involves a person's ability to rise from problems in psychology is called resilience. Resilience is the ability possessed by individuals to respond positively to a problem that is being faced. Factors that influence resilience are self-esteem and social support. Self-esteem is a person's assessment of himself, which consists of strength, courage, virtue, and competence. While social support is assistance from other people both in terms of material and emotional. This study aims to determine the effect of self-esteem and social support on resilience in female prisoners in the Madiun Class I prison, Indonesia. This study uses a type of quantitative research. The sample of this research is 22 people. Methods of data analysis in this study using multiple linear regression analysis. The results of multiple linear regression tests show that the effect of self-esteem and social support on resilience in female prisoners (WBP) in Class I prisons in Madiun is 14.2%, while the other 85.8% is influenced by other variables not discussed in the study.